Thumb Arthrodesis in The Arthritis Cases: A Scoping Review - Akbar, Ghifar; Kalanjati, Viskasari Pintoko; Wardhana, Teddy Heri ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Backgrounds: Osteoarthritis in the thumb is a common condition affecting men and women, especially postmenopausal women, causing pain, swelling, and reduced hand function. Arthrodesis is a treatment option for thumb arthritis, increasingly accessible in medical practice, though coverage remains limited. This article aims to review recent case reports on thumb arthrodesis in older people over the last three years, depicting the method's use and outcomes. Methods: After filtering per PRISMA-Sc guidelines on PubMed and the Journal of Hand Surgery (2020-2023), with additional manual filtering, four articles were found and analyzed using the JBI Critical Appraisal Checklist for Case Reports before inclusion. Result: Four case reports related to pollex arthrodesis in the last three years were published in PubMed. These include rare cases of bilateral thumb psoriatic arthritis, a novel surgical approach for nonunion after arthrodesis, and successful fusion using a vascularized bone graft. The limited number of articles may be attributed to the research cycle, shifting focus, and alternative treatments. With increased healthcare access and osteoarthritis prevalence, more people will seek treatment, potentially leading to increased arthrodesis procedures. Opportunities for new research include evaluating surgical techniques, biomaterials, and growth factors to enhance bone healing. Long-term follow-up studies remain crucial for identifying risk factors and improving patient outcomes in thumb arthrodesis. Conclusion: Despite limited research published in the last three years, arthrodesis remains a relevant treatment option for pollex conditions, with rising demand due to increasing osteoarthritis prevalence and healthcare access. Further research on surgical innovations and long-term outcomes is crucial.